Lysyl oxidase-like 2 (LOXL2), a new regulator of cell polarity required for metastatic dissemination of basal-like breast carcinomas - Moreno-Bueno, Gema (WILEY-VCH Verlag, 2011)
Basal-like breast carcinoma is characterized by the expression of basal/myoepithelial markers, undifferentiated phenotype, highly aggressive behaviour and frequent triple negative status (ESR−, PR−, Her2neu−). We have previously shown that epithelial–mesenchymal transition (EMT) occurs in basal-like breast tumours and identified Lysyl-oxidase-like 2 (LOXL2) as an EMT player and poor prognosis marker in squamous cell carcinomas. We now show that LOXL2 mRNA is overexpressed in basal-like human breast carcinomas. Breast carcinoma cell lines with basal-like phenotype show a specific cytoplasmic/perinuclear LOXL2 expression, and this subcellular distribution is significantly associated with distant metastatic incidence in basal-like breast carcinomas. LOXL2 silencing in basal-like carcinoma cells induces a mesenchymal-epithelial transition (MET) associated with a decrease of tumourigenicity and suppression of metastatic potential. Mechanistic studies indicate that LOXL2 maintains the mesenchymal phenotype of basal-like carcinoma cells by a novel mechanism involving transcriptional downregulation of Lgl2 and claudin1 and disorganization of cell polarity and tight junction complexes. Therefore, intracellular LOXL2 is a new candidate marker of basal-like carcinomas and a target to block metastatic dissemination of this aggressive breast tumour subtype.